MICELLAR-EXTRACTION PRECONCENTRATIОN OF ALUMINIUM AND FERRUM (III) BY THE NON-IONIC SURFACTANTS PHASES AT THE PRESENCE OF THE INDUCING ADDITION: UDC 543.3, 542.61, 611.185.10 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
The micellar extraction of the aluminium and ferrum complexes with the phase formation induced addition by micellar phases of thenon-ionic surfactants OP-10 and Triton X-100 was investigated. The influence of the concentration conditions, cationic surfactant andphenol on the phase separation parameter of aluminium and ferrum was established.
Keywords: -